QUALITY EVALUATION OF FRESH FINNED FISH (Thynnichthys thynnoides Blkr) PRESERVED WITH BITTER GOURD’S (Momordica charantia) EXTRACTS AT VARIED CONCENTRATIONS - Mardiana A Bakkara; Edison '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The objective of the research was to find out the quality of fresh finned fish (Thynnichthys thynnoides Blkr) which immersed in varied concentration of bitter gourd’s (Momordica charantia) extract. The optimum concentration of bitter gourd’ used to preserve the fish was determinated by the value of organoleptic test, total volatile base, total plate count and pH of the fish. The method used in this research used was experiment. Organoleptic test was analiyzed descriptively, while the total volatile base, total plate count, and pH were analyzed by using block randomized design (BRD). The result showed that the finned fish immersed in 30% bitter gourd’s extract was the best treatment which could restrain the freshness of finned fish for 12 hours. The organoleptic characteristic showed that the apparent of fish gills (6,5), the mocous of body surface (6,9), odor (6,8), texture (7,0), meat (color and visually) (7,1), total volatile base (14,4), total plate count (1,2x104 cfu/gr), and pH (6,9), meanwhile the appearance of fish eye of P0 was more accepted by panelists.Keywords: Finned fish, bitter gourd’s extract, quality, freshness, concentration